A comparison of physician emigration from Africa to the United States of America between 2005 and 2015 - Robbert J. Duvivier; Vanessa C. Burch; John R. Boulet (BMC, 2017)
Abstract Background Migration of health professionals has been a cause for global concern, in particular migration from African countries with a high disease burden and already fragile health systems. An estimated one fifth of African-born physicians are working in high-income countries. Lack of good data makes it difficult to determine what constitutes "African" physicians, as most studies do not distinguish between their country of citizenship and country of training. Thus, the real extent of migration from African countries to the United States (US) remains unclear. This paper quantifies where African migrant physicians come from, where they were educated, and how these trends have changed over time. Methods We combined data from the Educational Commission for Foreign Medical Graduates with the 2005 and 2015 American Medical Association Physician Masterfiles. Using a repeated cross-sectional study design, we reviewed the available data, including medical school attended, country of medical school, and citizenship when entering medical school. Results The outflow of African-educated physicians to the US has increased over the past 10 years, from 10 684 in 2005 to 13 584 in 2015 (27.1% increase). This represents 5.9% of all international medical graduates in the US workforce in 2015. The number of African-educated physicians who graduated from medical schools in sub-Saharan countries was 2014 in 2005 and 8150 in 2015 (304.6% increase). We found four distinct categorizations of African-trained physicians migrating to the US: (1) citizens from an African country who attended medical school in their own country (86.2%, n = 11,697); (2) citizens from an African country who attended medical school in another African country (2.3%, n = 317); (3) US citizens who attended medical school in an African country (4.0%, n = 537); (4) citizens from a country outside Africa, and other than the United States, who attended medical school in an African country (7.5%, n = 1013). Overall, six schools in Africa provided half of all African-educated physicians. Conclusions The number of African-educated physicians in the US has increased over the past 10 years. We have distinguished four migration patterns, based on citizenship and country of medical school. The majority of African graduates come to the US from relatively few countries, and from a limited number of medical schools. A proportion are not citizens of the country where they attended medical school, highlighting the internationalization of medical education.